Peningkatan Kesadaran Masyarakat Tentang Anemia dan Pencegahan Stunting di Masa Depan Melalui Aplikasi Anemiago - Sabran Sabran; Dian Kartika Sari; Malinda Capri Nurul Satya (Journal of Community Development, 2025)
Anemia is a condition where the level of HB or hemoglobin in the blood is less than the normal standard. Based on the 2018 Riskesdas data, the prevalence of anemia in women aged ≥15 years (adolescent girls) was 41.6% while the prevalence of anemia in pregnant women was 48.9%. This figure has increased from 31% in 2013. Adolescent girls who suffer from anemia are at risk of anemia during pregnancy which will potentially increase stunting rates. The impact of anemia on adolescent girls is stunted growth, easily infected, decreased academic achievement, becoming a high-risk prospective mother for pregnancy and childbirth. Anemia that occurs in women of childbearing age is a challenge in the field of reproductive health nutrition. With the development of technology in this day and age, it is certainly unfortunate if it is not used to provide positive values to the community. Therefore, the development of the AnemiaGo application for early detection of anemia is very important. This is done to increase public awareness about anemia and reduce the incidence of anemia early. The method used in this community service is planning and implementing activities consisting of introductions, counseling by providing education and training, giving Blood Additive Tablets (TTD) and assessing by giving pretest and posttest questionnaires. The results obtained from this activity are an increase in knowledge and attitudes in adolescents and WUS.